West Nile neuroinvasive disease. Report of four cases in Northern Greece, 2018. Issue 8 (11th March 2020) - Papagiannis, Ioannis; Tsolaki, Magda; Kiryttopoulos, Andreas; Antoniadi, Eleni; Kyriakogianni, Chrysanthi; Fotiou, Dimitrios; Notas, Konstantinos; Liougka, Evangelia; Myrou, Athina; Hatzitolios, Apostolos; Haloudis, Pantelis; Papaioannou, Maria; et al.
Abstract: West Nile virus (WNV) is a mosquito‐borne RNA flavivirus which caused several epidemics worldwide. The year 2018 was a WNV record year for Europe, including Greece, with earlier and longer transmission season with higher than the previous number of cases. It has been proposed that some simple biochemical markers may be helpful for the recognition of WNV neuroinvasive disease, its differential from other neurological infectious diseases and prognosis. We describe four cases that suffered from WNV meningitis and/or encephalitis hospitalized in 2018 in a tertiary hospital in Thessaloniki, Greece, and investigate the importance of simple biomarkers for the recognition of WNV etiology. Highlights: 2018 was a record year for WNV with a total number of 2083 reported infections in Europe 316 cases (47 fatal) of WNV infection were reported in 2018 in Greece; 241 of them were cases with neuroinvasive disease. Central nervous system (CNS) involvement consists of West Nile Meningitis (WNM), West Nile Encephalitis (WNE), or acute flaccid paralysis. ESR to CRP ratio higher than 1 might lead towards the diagnosis of WNE.